Employment and productivity growth in Tanzania’s service sector - Ellis, Mia; McMillan, Margaret S.; Silver, Jed (Oxford University Press, 2019)
During 2002–12, Tanzania’s economy grew more rapidly than at any other time in its history. More than three-quarters of its labour productivity growth is accounted for by structural change; the remainder is largely attributable to within-sector productivity growth in agriculture. The growth attributable to structural change is almost entirely explained by a rapid decline in the agricultural employment share and an increase in the non-agricultural private sector employment share—with 11.4% of employment growth in the private non-agricultural economy due to the expansion of the formal private sector; the remaining 88.6% occurred in the informal sector. This chapter assesses the role that services have played in Tanzania’s recent growth and the role that they could play in its economic future.